Students’ perception toward effective teaching approach used by EFL teacher - Rezkiah Hartanti; Adamu Babikkoi; Iskandar (Center for Humanities and Innovation Studies, 2018)
This research aimed to describe the approach of effective and ineffective teaching approaches used by EFL teacher as perceived by the students. This research was designed using qualitative research. This research applied the purposive sampling technique by considering students’ English Achievement. The subject of this research was the seventy-five students of the secondary school in Maros regency, South Sulawesi, Indonesia. The data was collected through class discussion and focus group discussion. In analyzing the data, the researchers used qualitative data analysis. The results of this research suggest EFL teachers’ use four effective teaching approaches used by EFL teachers in secondary school; they are communicative, cooperative learning, audio-lingual, and simulation and games. The students believed these approaches stimulate the students’ activeness and participation in the classroom. There are three ineffective teaching approaches used by EFL teachers in secondary school; they are lecturing, grammar translation, and direct teaching.